PRAYER’S REGULATION WITH LEVEL OF ANXIETY IN ELDERLY IN PSTW BUDHI LUHUR BANTUL - Achmad Misbakhul Munir; Dina Putri Utami Lubis; Salis Miftahul Khoeriyah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Mental health problems that often appear in elderly is anxieties that happens countinously for a long time, it can make very severe exhaustion and event death. The purpose of this study was to identifi ed the correlation prayer’s regulation with level of anxiety to continue age in PSTW budhi luhur bantul. Method. The method used in this study was an analytic survey with cross sectional approach. Engineering samples were taken mainly by using purposive sampling. Test the validity used the formula koefesien biserial correlation and reliability testing using the Kuder-Richardson (KR20). Result. Statistical analysis test used the formula Kendall-Tau. This study showed that there was a correlation between regularity of prayer with the level of anxiety in the elderly in PSTW Budi Luhur Bantul shown from the value of the correlation Kendall-Tau (τ) = 0.585 with p value of 0.000. Discussion. It was recommended to PTSW Budhi Luhur Bantul more intensive to accompany elderly in pray activities.Keywords: Regularity Prayer, Anxiety, Elderly.